Quantitative Analysis of Multi-components in Curcuma xanthorrhiza by Single Marker - Hera Nirwati; Badrunanto Badrunanto; Wulan Tri Wahyuni; Mohamad Rafi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
A new simple and effective routine analytical method for quantification of curcuminoids in Curcuma xanthorrhiza was developed by high-performance liquid chromatography. This method based on chromatographic fingerprint combined with a quantitative analysis of multi-components by single marker (QAMS). Curcumin was selected as an internal marker for the determination of two other similar compounds, i.e. bisdemethoxycurcumin and demethoxycurcumin, by using the relative coefficient factor (RCF). Excellent linearity was obtained for each component (r2 > 0.9998), and the recovery of extraction methods were within 100.23-103.95%. The precision of the method was good at inter-day and intra-day analysis (RSD < 4.0%). The stability of RCFs was good under various chromatographic conditions with RSD < 1%, and the ratio of retention time was used to locate each compound. The quantification of curcuminoids between QAMS and external standard method (ESM) proved the consistency and similarity of the two method (RSD < 2%). This study demonstrated that QAMS could be used as a routine method for quality control of curcuminoids in C. xanthorrhiza. This method successfully proved accurate, stable, more effective and simple than external standard method.